Mamíferos de Médio e Grande Porte de Uma RPPN No Município de Jaú, Estado de São Paulo - Reale, Ricardo [UNESP] (Universidade Estadual Paulista (Unesp), 2011)
The medium to large-sized mammals make population control of invertebrates and vertebrates, as well as seed dispersers are also important. Are losing territory and living area because of deforestation and fragmentation of natural areas, mainly in the Atlantic Forest. The RPPN Amadeu Botelho, in the municipality of Jaú, São Paulo State, is one of the last forest remnants of interior paulista. It is isolated from other forest fragments and thus is a wildlife refuge in the region of Jaú, Midwest of the State. Animals as Pumas (Puma concolor), ocelot (Leopardus pardalis), cat-Moorish (Puma yagouaroundi), have already been sighted in the reserve by officials and residents. The buffer property of the farm Santo Antônio dos Ipês, is surrounded by several plantations, and is very close to the Centre of the city of Jaú. In addition to the lifting of the reservation, it sized mammal species diagnosed the influences that the activities of the farm and the proximity to the Centre of the municipality of Jaú exert to fauna studied

Os mamíferos de médio e grande porte fazem o controle populacional de invertebrados e vertebrados, bem como também são importantes dispersores de sementes. Estão perdendo território e área de vida por causa do desmatamento e da fragmentação de áreas naturais, principalmente na Mata Atlântica. A RPPN Amadeu Botelho, no município de Jaú, Estado de São Paulo, é um dos últimos remanescentes florestais do interior paulista. Fica isolado de outros fragmentos florestais e, portanto, é um refúgio da vida silvestre na região de Jaú, centro-oeste do estado. Animais como onça-parda (Puma concolor), jaguatirica (Leopardus pardalis), gato-mourisco (Puma yagouaroundi), já foram avistados na reserva por funcionários e moradores. A reserva, propriedade da fazenda “Santo Antônio dos Ipês”, é cercada por diversas plantações e está muito próxima ao centro da cidade de Jaú. Além de fazer o levantamento da mastofauna da reserva, este trabalho diagnosticou as influências que as atividades da fazenda e a proximidade com o centro do município de Jaú exercem para a fauna estudada
Keywords: Mamífero; Reservas florestais; Ecologia florestal; Mastozoologia